Study the Drying Behavior of Red Pepper (Capsicum annuum L.) - Anjaneyulu, A.; Sharangi, A. B. (International Journal of Bio-resource and Stress Management, 2022)
The experiment was carried out in the laboratories of the Department of Food Engineering and the Department of Plantation Spices Medicinal & Aromatic Crops, and the Central Horticultural Laboratories, Bidhan Chandra Krishi Viswavidyalaya, West Bengal, India during 2018−2019 and 2019−2020. With an objective of study the performance of drying methods at different temperatures on physical and quality parameters of dry chilli. The experiment was conducted in Randomized Complete Block Design (RCBD) replicated thrice with seven treatments of different drying methods viz., sun drying, solar drying and oven drying at 50°C, 55°C, 60°C, 65°C and 70°C. The experimental results were maximum fruit length (7.00 cm), fruit diameter (10.22 mm), chroma (38.13), minimum total color difference (11.82) and browning index minimum (85.81) were found in the oven drying at 65oC and the fruit weight (0.81 g) was maximum observed in the sun drying method. However, the minimum bulk density (0.31 g cc-1) and the maximum dehydration ratio (3.88) were detected by oven drying at 70°C. The highest β-carotene content (224.41 µg 100 g-1) was observed during oven drying at 50°C, where as minimum β carotene content was recorded by sun drying. In sun drying method low quality due to oxidation as the dried chilli was exposed directly to light and sun. An increase in drying air temperature and long period of drying time has a negative effect on quality of dry chilli.